ANALISIS ANGGARAN RESPONSIF GENDER DI PROVINSI SUMATERA SELATAN - Dwi Oktaria (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2015)
This study aimed at analyzing the implementation of proposed document plan and the realization of budgeting toward gender bias in the province of South Sumatra. The technique used on analyzing gender bias is descriptive statistics. Based on assessment of proposed document plan and realization of budgeting, the result shows that the programme tend to support budgeting responsive gender.